Archaeology : the essential guide to our human past - Bahn, Paul G. (Smithsonian Books, 2017)
"Epic in scope, yet filled with detail, this illustrated guide takes readers through the whole of our human past. Spanning the dawn of human civilization through the present, it provides a tour of every site of key archaeological importance. From the prehistoric cave paintings of Lascaux to Tutankhamun's tomb, from the buried city of Pompeii to China's Terracotta Army, all of the world's most iconic sites and discoveries are here. So too are the lesser-known yet equally important finds, such as the recent discoveries of our oldest known human ancestors and of the world's oldest-known temple, Gobekli Tepe in Turkey. A masterful combination of succinct analysis and driving narrative, this book also addresses the questions that inevitably arise as we gradually learn more about the history of our species. Written by an international team of archaeological experts and richly illustrated throughout, Archaeology: A Comprehensive Guide to Our Human Past offers an unparalleled insight into the origins of humankind"--